Factors Influencing Smallholder Farmers Adoption of Eucalyptus Woodlot in Wogera District, North Gondar Zone, Amhara Regional State of Ethiopia (International Journal of Scientific Research and Management (IJSRM), 2018)
Eucalyptus is familiar specious in various weather conditions of the world. Eucalyptus woodlot planation in wogera district become increased since 1970. The study was to examine the determinant factors for the adoption of eucalyptus woodlots by smallholder farmers in Wogera district. Three stage sampling procedure was used to select 118 sample respondent farmers from three purposively selected Kebeles of the district. Household survey was used to collect quantitative data. Econometric model (binary logit model) was employed to analyze the quantitative data. Adoption of eucalyptus woodlot was affected negatively by family size and fertility of land, and positively affected by farm size, access to market, and farmers’ perception towards eucalyptus woodlot production. It is concluded that adoption of eucalyptus woodlot plantation was affected mainly by socio-economic and institutional factors. Therefore, attention should be given to manage the identified factors and change smallholder farmer’s attitude towards eucalyptus woodlot plantation.